A taxonomic revision of the genus Dolomiaea (Asteraceae: Cardueae) in India - Kasana, S.; Uniyal, P. L.; Pandey, A. K. (Rheedea, 2026)
The genus Dolomiaea DC. (Asteraceae: Cardueae) is represented by three species in India. It is distributed in the alpine Himalaya and is often found in chasmophytic habitats. Recent advances in molecular phylogenetic studies have re-circumscribed the generic boundaries of Dolomiaea and hence a detailed taxonomic account of this genus in India is provided here. We recognize three species: Dolomiaea baltalensis Dar & Naqshi, D. costus (Falc.) Kasana & A.K.Pandey and D. macrocephala DC. ex Royle for India. Dolomiaea macrocephala and the heterotypic synonym of D. costus, Aplotaxis lappa Decne. are lectotypified.